Sex Differences in Profile and In‐Hospital Death for Acute Stroke in Chile: Data From a Nationwide Hospital Registry - Marilaura Nuñez; Ma.Ignacia Allende; Francisca González; Gabriel Cavada; Craig S. Anderson; Paula Muñoz Venturelli (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Knowledge of local contextual sex differences in the profile and outcome for stroke can improve service delivery. We aimed to determine sex differences in the profile of patients with acute stroke and their associations with in‐hospital death in the national hospital database of Chile. Methods and Results We present a retrospective cohort based on the analysis of the 2019 Chilean database of Diagnosis‐Related Groups, which represents 70% of the operational expenditure of the public health system. Random‐effects multiple logistic regression models were used to determine independent associations of acute stroke (defined by main diagnosis International Classification of Diseases, Tenth Revision [ICD‐10] codes) and in‐hospital death, and reported with odds ratios (ORs) and 95% CIs. Of 1 048 575 hospital discharges, 15 535 were for patients with acute stroke (7074 [45.5%] in women), and 2438 (15.6%) of them died during hospitalization. Differences by sex in sociodemographic and clinical characteristics were identified for stroke and main subtypes. After fully adjusted model, women with ischemic stroke had lower in‐hospital death (OR, 0.79 [95% CI, 0.69–0.91]) compared with men; other independent predictors included age per year increase (OR, 1.03 [95% CI, 1.03–1.04]), chronic kidney disease (OR, 1.47 [95% CI, 1.20–1.80]), atrial fibrillation (OR, 1.50 [95% CI, 1.26–1.80]), and other risk factors. Conversely, for intracerebral hemorrhage, women had a higher in‐hospital mortality rate than men (OR, 1.19 [95% CI, 1.02–1.40]); other independent predictors included age per year increase (OR, 1.009 [95% CI, 1.003–1.01]), chronic kidney disease (OR, 1.55 [95% CI, 1.23–1.97]), oral anticoagulant use (OR, 1.88 [95% CI, 1.37–2.58]), and other risk factors. Conclusions Sex differences in characteristics and in‐hospital death of hospitalized patients exist for acute stroke in Chile. In‐hospital death is higher for acute ischemic stroke in men and higher for intracerebral hemorrhage in women. Future research is needed to better identify contributing factors.